2018
DOI: 10.5204/ssj.v9i2.419
|View full text |Cite
|
Sign up to set email alerts
|

Front loading the curriculum: early placement experiences enhance career awareness and motivation

Abstract: Deciding which career path is right for undergraduate students can be challenging and positive outcomes are linked to early work placements.  The aim of the current study was to explore the student experience following the introduction of early career-based awareness-raising and reflective learning opportunities in first-year sport and exercise science-based students.  Students met with the first-year coordinator to discuss career progression and career aspirations. From this meeting, students were allocated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Evaluation of both student and facilitator responses indicated that the timing of the workshop may limit the students' ability to apply any benefits gained from the workshop to their program of study. This was supported by students who indicated that they would have benefited from WIL opportunities and career pathway information earlier or more frequently during their degree, consistent with previous research undertaken in exercise and sports science students (de Hollander et al, 2018). This would enable them to make more informed decisions on elective subjects and extra-curricular WIL experiences.…”
Section: Discussionsupporting
confidence: 72%
“…Evaluation of both student and facilitator responses indicated that the timing of the workshop may limit the students' ability to apply any benefits gained from the workshop to their program of study. This was supported by students who indicated that they would have benefited from WIL opportunities and career pathway information earlier or more frequently during their degree, consistent with previous research undertaken in exercise and sports science students (de Hollander et al, 2018). This would enable them to make more informed decisions on elective subjects and extra-curricular WIL experiences.…”
Section: Discussionsupporting
confidence: 72%
“…Previous research amongst students studying exercise and sports science- related degrees has shown that providing students with career-related experiences early in their degree (e.g. work placement) can increase awareness of potential careers that may be pursued after graduation (de Hollander et al, 2018). Although not discounting the value of work placement experience, our findings suggest that students may gain career exploration skills via an online module, which could either be used to supplement the experience of work placement, or utilised when work placement is not able to be offered in existing courses.…”
Section: Explorationmentioning
confidence: 99%
“…Universities hold a responsibility to provide opportunities for students to develop their career planning skills. One such approach is to embed career planning into the curriculum, which may be particularly important for students in broad vocational courses, such as health or exercise and sports science degrees (de Hollander, McGuckin, Sinclair, Barnett, & Sealey, 2018), for which career paths may be more challenging to define. Although career education programs have been shown to result in improvements in career planning amongst high school students (Miles, 2008;Syed-Mohamad, 2005), few studies have examined the impact of such approaches for university students (Talib, Salleh, Amat, Ghavifekr, & Ariff, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research have indicated the importance of career awareness at all ages, and that it has been a central concern for more than half a century (Hashish, 2019;de Hollander et al, 2018;Cohen et al, 2013;Fouad et al, 2006;Kemple et al, 1999;Dorr and Lesser, 1980;Wise et al, 1976). Raising career awareness is an important element for improving degree completion (Department of Education and Training, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to provide additional opportunities to students where they can learn about different career paths that may emerge from their degrees. A common approach for raising career awareness is the participation of industry in higher education (de Hollander et al, 2018;Sarkar et al, 2016;Zegwaard and Coll, 2011).…”
Section: Introductionmentioning
confidence: 99%